The production of Oithona similis (Copepoda: Cyclopoida) in the Southern Ocean - Fransz, H. G.; Gonzalez, S. R. (ICES Journal of Marine Science, 1995)
Seasonal variation in abundance and biomass of different instars of Oithona similis was studied for stations in the Weddell Sea and the Antarctic Circumpolar Current south of 60°S sampled in different years. Egg production was more spread over the seasons than in most calanoid copepod species and the mean stage was more constant, indicating a mixing of age classes and overlap of generations. Juvenile stages increase in abundance between October and January, but the main development of copepodids was between January and May. A minimum estimate of daily growth rate of 1.5% body weight corresponds with a development from Nauplius 1 to Copepodite 5 between 1 November and 30 May and leads to an annual Production/Biomass (P/B) ratio of 3.3. The mean population biomass in the southern waters was 150 mgC m−2 in the epipelagic zone and the minimum estimate of annual production 0.5 gC m−2. Because the contribution of the species to zooplankton biomass in the Southern Ocean may be higher than elsewhere and the annual P/B is generally much higher than in the larger calanoid species, the production of Oithona similis may be the highest of all zooplankton species in the Antarctic region.